PEMBUATAN BAHAN AJAR BERBASIS MODUL PADA MATAKULIAH MEDIA PEMBELAJARAN DI JURUSAN TARBIYAH STAIN SULTAN QAIMUDDIN KENDARI - Ambar Sri Lestari (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2014)
Media in teaching and learning is one module in the form of teachingmaterials. Teaching materials are all kinds of materials that are used tohelp teachers / instructors in carrying out teaching and learningactivities in the classroom. Modules can be viewed as a medium or asteaching material, but in this study modules are seen as the mediumused to convey the material teachers. The module is a tool or a learningtool containing materials, methods, limitations, and how to evaluatesystematically designed and appealing to attain competency / subcompetencies expected in accordance with the level of complexity.Keywords: Modules, Subjects, Learning Media